How Religious tradition Survives in the World of Science: John Polkinghorne and Norbert Samuelson - Moore, James F. (Zygon, 1997)
The Faith of a Physicist: Reflections of a Bottom-Up Thinker John Polkinghorn Judaism and the Doctrine of Creation Norbert Samuelson